Laporan Keuangan Pada UMKM di Desa Klambir Lima Kebun Kecamatan Hamparan Perak - Teuku Radhifan Syauqi; Destari Damanik; Hanif Ramadhan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study is two parts, namely: Assessing the obstacles that hinder businesses in implementing financial recording and difficulties in preparing financial reports in accordance with the Financial Accounting Standards for Micro, Small, and Medium Enterprises (SAK EMKM). Preparing financial reports for Micro, Small, and Medium Enterprises (MSMEs). This study uses a qualitative method with a case study method. The conclusion is that the bag craftsman owned by Mrs. Indra Suriyanti has not been able to prepare financial reports and carry out the accounting cycle properly, this is due to the limitations of the owner as the person responsible for the finances of business activities who do not understand and the absence of human resources who are experts in the field of accounting to be involved in providing insight and training to the owner.